How to feed the cities? Co-creating inclusive, healthy and sustainable city region food systems - Säumel, Ina; Reddy, Suhana; Wachtel, Thomas; Schlecht, Martin; Ramos-Jiliberto, Rodrigo (Frontiers in Sustainable Food Systems, 2022)
People drive transitions. Current urban living conditions, specifically food systems, challenge the health, wellbeing and coherence of individuals and whole societies, and for effective change toward resilient communities, people need to reinvent the way they produce, distribute and consume food. Consequently, in their communities' people are creating foodscapes and governing the transition toward sustainable local food systems. Here, we introduce a conceptual framework to develop this transformation through empowering the urban multi-stakeholder society as the agent of this process. To do so, we reviewed scientific evidence and experiences from seven selected City Regions (Albacete, Baku, Dresden, Izmir, Ljubljana, Megara, and Valparaiso) as case studies and conducted a SWOT analysis to explore the capacity of food systems to enhance multi-functionality of urban landscapes, with special focus on social cohesion and quality of life. We grasp existing policies; hone them and leverage policies and strategies toward human-centered actions for future proofing food systems.